PM(2.5) in Urban and Rural Nursery Schools in Upper Silesia, Poland: Trace Elements Analysis - Mainka, Anna (Int J Environ Res Public Health, 2015)
Indoor air quality (IAQ) in nursery schools is an emerging public health challenge. Particular attention should be paid to younger children, because they are more vulnerable to air pollution than older children. Among air pollutants, fine particulate matter (PM(2.5)) is of the greatest interest mainly due to its strong association with acute and chronic effects on children’s health. In this paper, we present concentrations of PM(2.5) and the composition of its trace elements at naturally ventilated nursery schools located in the area of Gliwice, Poland. The nursery schools were selected to characterize areas with different degrees of urbanization and traffic densities during the winter and spring seasons. The results indicate there is a problem with elevated concentrations of PM(2.5) inside the examined classrooms. The children’s exposure to trace elements was different based on localization and season. PM(2.5) concentration and its trace element composition have been studied using correlation coefficients between the different trace elements, the enrichment factor (EF) and principal component analysis (PCA). PCA allowed the identification of the three components: anthropogenic and geogenic sources (37.2%), soil dust contaminated by sewage sludge dumping (18.6%) and vehicular emissions (19.5%).